Sexual harassment in the workplace - Slabbert, Yvette (Centre for Law and Society, 2024)
The twentieth century has brought substantial changes in the legal and socioeconomic status of women. Women have entered the labour market in substantial numbers, hoping for recognition as persons in their own right, based on their individual capabilities and achievements in their chosen realms of endeavour.